PERTUMBUHAN PROPAGUL BAKAU (Rhizophora apiculata BL) DENGAN PERBEDAAN JENIS AIR SIRAMAN DAN MEDIA TANAM DI PERSEMAIAN PT. BINA OVIVIPARI SEMESTA - Pangestika, Laras; Burhanuddin, . (Universitas Tanjungpura, 2018)
The purpose of this research is to find out the media are suitable as a medium growth of mangrove and knowing the time of appearance of first leaf. Object of research is mangrove propagul PT. Bina Ovivipari universe. The medium used is the land of the mud and soil ultisol. This research was carried out on the seedbed of PT Bina Ovivipari universe. The research method used complete randomized factorial experiments (Factorial RAL) with 4 combination treatment. The observation parameters is percentage grow plants Rhizhopora apiculata, the time of the emergence of the first leaf, and the time needed for the plant to be ready for planting. The treatment of the soil with plain water mud had a pretty good growing percent i.e. of 60% while on the treatment of the soil with plain water ultisol percent grow only 40% which based on the results of calculations using factorial RAL indicates that on a spray of sea water have different results by using plain water spray where on ordinary water spray has a real influence on the growth of R.apiculata so that spray water on the media as well as media ultisol soil sea mud can be used for the growth of propagul until the fourth week of planting.Keyword: Mangrove Propagul, Ultisol Soil, Type of Water